2020
DOI: 10.14744/nci.2020.31391
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Coronary Artery Disease and SIRT1 Protein

Abstract: Endothelial cell dysfunction proceeding with increased inflammation and monocyte increase is one of the main causes of vessel injury in CAD. SIRT1 (Sirtuin 1) protein plays an important role in the regulation of cellular physiological mechanisms. SIRT1 has roles in regulating angiogenesis and preventing endothelial dysfunction and reperfusion injury due to ischemia. Suppression of SIRT1 causes monocyte affinity due to endothelial dysfunction. Sirtuins activators are involved in pathologies of many diseases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Silent information regulator 1 (SIRT1) is a transcriptional regulator with histone deacetylase activity, which can sense the energy status of the body, regulate the expression of other transcription factors, and also participate in the process of regulating cellular metabolic homeostasis [ 32 ]. SIRT1 promotes the deacetylation of lysine residues of PGC-1 α , initiates the transcriptional activity of PGC-1 α , and regulates its expression, which further regulates cellular energy metabolism and mitochondrial biosynthesis and protects cardiomyocytes from oxidative stress [ 33 ]. ATP5D is a subunit of ATP synthase involved in oxidative phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Silent information regulator 1 (SIRT1) is a transcriptional regulator with histone deacetylase activity, which can sense the energy status of the body, regulate the expression of other transcription factors, and also participate in the process of regulating cellular metabolic homeostasis [ 32 ]. SIRT1 promotes the deacetylation of lysine residues of PGC-1 α , initiates the transcriptional activity of PGC-1 α , and regulates its expression, which further regulates cellular energy metabolism and mitochondrial biosynthesis and protects cardiomyocytes from oxidative stress [ 33 ]. ATP5D is a subunit of ATP synthase involved in oxidative phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the control group, Bcl-2 expression was reduced, while Bax and cleaved caspase-3 expressions were increased in the LPS group, which were partially reversed by miR-197 inhibitor ( p < 0.01) (Figures 2(d) and 2(e) ). Based on a previous study identifying the pivotal role of SIRT1 in protecting cardiomyocytes from oxidative stress injury [ 24 ], we subsequently determined the expression of SIRT1 in H9c2 cells. Western blot and qRT-PCR revealed that LPS notably downregulated SIRT1 expression, which was reversed via miR-197 inhibition ( p < 0.001) (Figures 3(a) – 3(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…It regulates angiogenesis, and it protects the endothelium against dysfunctional changes and damage to the heart muscle resulting from a reduced perfusion and ischemia. Suppression of the SIRT1 causes monocyte affinity due to endothelial dysfunction [ 53 ]. The gene encoding transcription factor TCF21 has been linked to CAD risk by GWAS in multiple racial/ethnic groups.…”
Section: Coronary Artery Disease and Atherosclerosismentioning
confidence: 99%